Kinerja BUMN Dalam Menyediakan Barang dan Jasa Publik: Antara Fungsi Sosial dan Komersial - Sitorus, Satrio Setiawan; Arinda, Gistrant Yoga; Zein, Ahmad Wahyudi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
SOEs have two main roles: serving the community (social function) and generating profits (commercial function). Unfortunately, these two functions often clash, because if the focus is on public service, profits can be thin, even losses. But if the focus is on profit, it is feared that it will sacrifice public interests. This study discusses how SOEs in Indonesia carry out these two functions simultaneously, what are the challenges, and strategies so that they can continue to run in balance. Using a qualitative literature study method, data from reports and articles are used to analyze real conditions in the field. The results show that the dual role of SOEs can run, as long as there is professional management, clear regulations, and appropriate government support.